Woodfordia fruticosa fermented with lactic acid bacteria impact on foodborne pathogens adhesion and cytokine production in HT-29 cells - Lee, Eon-Bee; Lee, Kyubae (Frontiers in Microbiology, 2024)
Investigating foodborne pathogens and their impact on human health, especially their interaction with intestinal cells, is an essential research area. The role of lactic acid bacteria (LAB) in enhancing gut microbial equilibrium, suppressing harmful bacteria, and bolstering gut health is increasingly recognized. This study examined the effects of fermenting Woodfordia fruticosa (WF), known for its antimicrobial properties against gastrointestinal pathogens, with LAB. It specifically looked at how this fermentation impacted the adherence of foodborne pathogens to the intestinal lining and cytokine production, with the goal of improving gut health and managing foodborne infections in HT-29 cells. The results showed enhanced antimicrobial effects post-fermentation of WF with various LAB strains. Notably, WF fermented with LAB (WFLC) significantly reduced the adhesion of pathogens like L. monocytogenes (6.87 ± 0.33 %) and V. parahaemolyticus (6.07 ± 0.50 %) compared to the control. Additionally, WFLC demonstrated an ability to increase IL-6 production in response to pathogens such as E. coli O157:H7 (10.6 %) and L. monocytogenes (19 %), indicating potential immune-activating properties. Consequently, WF fermented with LAB could be a promising new method for combating foodborne pathogens. However, further research is needed to fully understand WF's phytochemical composition and its role in these effects.The study into the interplay between foodborne pathogens and human health, particularly their effects on intestinal cells, is crucial. The importance of lactic acid bacteria (LAB) in promoting a healthy balance of gut microbiota, inhibiting harmful bacteria, and supporting overall gastrointestinal health is becoming more apparent. Our study delved into the impact of fermenting Woodfordia fruticosa (WF), a plant known for its antimicrobial properties against gastrointestinal pathogens, with LAB. We focused on the influence of this fermentation process on the binding of foodborne pathogens to the gut lining and cytokine production, aiming to enhance gut health and control foodborne infections in HT-29 cells. Post-fermentation, the WF exhibited improved antimicrobial effects when combined with different LAB strains. Remarkably, the LAB-fermented WF (WFLC) substantially decreased the attachment of pathogens such as L. monocytogenes (6.87 ± 0.33%) and V. parahaemolyticus (6.